DIGITAL MARKETING MENTORING FOR THE MSME ELJOGJAWI_BATIKSANTRI VIA THE TIKTOK PLATFORM - Ahmad Hudaifah; Agustinus Tri Wicaksono; Arnoldus Yansen Kopong Samon; Naima Andleeb (EMPOWERING HUMANITY, 2025)
Digital marketing assistance for the MSME "Eljogjawi Batiksantri" in Yogyakarta was conducted to optimize the use of TikTok as a platform for creative content-based marketing. The initiative was prompted by low view counts and engagement levels on the @eljogjawiofficialstore TikTok account, which directly impacted brand awareness and sales. The assistance employed in-depth interviews and a "learning-by-doing" approach, grounded in the theoretical frameworks of Uses and Gratifications (U&G), Customer Relationship Management (CRM), and Experiential Learning Theory. The process was guided by Ki Hajar Dewantara’s philosophy of *Ngerti, Ngrasa, Nglakoni* (3N) emphasizing understanding, reflection, and concrete action. Results showed an increase in capacity and a shift in the MSME owner's mindset from a product-centric orientation to one focused on value and customer experience. However, technical limitations on the TikTok Business account specifically restrictions on using trending audio were a primary factor hindering content performance. These findings underscore that the success of an MSME's digital strategy depends not only on content creativity but also on a deep understanding of the technical and algorithmic characteristics of the digital platforms employed.